Fault Aware Energy Efficient Mechanisms in Cloud: A Comprehensive Survey - Sunila,; Kaur, Kamaljit (International Journal of Computer Sciences and Engineering, 2025)
The energy consumption within cloud increases as fault or failure encountered within cloud computing. This paper presents the analysis of mechanisms used to decrease the energy consumption and enhances fault tolerance degree. The mechanisms which are discussed include both proactive and reactive fault tolerance. This study presents the comparatives analysis of techniques used to ensure fault tolerance and parameters which are enhanced through the application of the techniques. The modification to the existing techniques is required which is concluded through this proposed survey. VM Migration strategies are followed in order to migrate the load on the fittest virtual machine. This happens only if fault appears within the virtual machine. To preserve the VMs against the faults parametric comparison of existing techniques is required. Parametric enhancement is critical in future work.